Impact of Wines and Wine Constituents on Cyclooxygenase-1, Cyclooxygenase-2, and 5-Lipoxygenase Catalytic Activity - Zsofia Kutil; Veronika Temml; David Maghradze; Marie Pribylova; Marcela Dvorakova; Daniela Schuster; Tomas Vanek; Premysl Landa (Hindawi Limited, 2014)
Cyclooxygenases and lipoxygenases are proinflammatory enzymes; the former affects platelet aggregation, vasoconstriction, vasodilatation and later the development of atherosclerosis. Red wines from Georgia and central and western Europe inhibited cyclooxygenase-1 (COX-1) activity in the range of 63-94%, cyclooxygenase-2 (COX-2) activity in the range of 20-44% (tested at a concentration of 5 mL/L), and 5-lipoxygenase (5-LOX) activity in the range of 72-84% (at a concentration of 18.87 mL/L). White wines inhibited 5-LOX in the range of 41-68% at a concentration of 18.87 mL/L and did not inhibit COX-1 and COX-2. Piceatannol (IC50 = 0.76 μM) was identified as a strong inhibitor of 5-LOX followed by luteolin (IC50 = 2.25 μM), quercetin (IC50 = 3.29 μM), and myricetin (IC50 = 4.02 μM). trans-Resveratrol was identified as an inhibitor of COX-1 (IC50 = 2.27 μM) and COX-2 (IC50 = 3.40 μM). Red wine as a complex mixture is a powerful inhibitor of COX-1, COX-2, and 5-LOX, the enzymes involved in eicosanoid biosynthetic pathway.